“Exploring perceptions of dog walking among middle-class black people that walk dogs” - Mhlongo, Nkululeko Benedict (My University, 2020)
The black middle-class has grown exponentially since democratisation. While research on the black middle-class has kept a pace of various permutations of this growth as well as those kept out of the mainstream economy by high unemployment rates, much less scholarship has been undertaken to explore the identity implications of class transitions. Beginning with anecdotal accounts about the aspirations of black middle-class people, with dog walking as the point of entry, this study sort to understand the meanings attached to dog walking from the perspective of ten middle-class black people who walk their dogs. The findings present a complex picture that suggests that we should nuance our understandings of black middle-class people in order to recognize the continuities and discontinuities with the black working class. While some resisted the idea of dog walking as a performance of middle-classness, the findings suggest that performativity is always at play in the social practice of dog walking. Secondly, the study found that he middle-class position is highly contested among black people ostensibly living middle-class lives in the suburbs of Johannesburg. This points to the instability of class identifications when understood in relation to over determined racialized identity and solidarity in South Africa. Lastly, the research presents the multiple roles that dogs and dog walking plays in the black middle-class family. The implications of this research suggest that more creative and nuanced ways of understanding the South African black middle-class are necessary in order to imbue this group with the complexity characteristic of people as they participate in everyday life
A thesis submitted in partial fulfilment of the requirements for the degree of Masters in Community-based Counselling Psychology in the Faculty of Humanities, University of the Witwatersrand, 2020